Truncation and Activation of Dual Specificity Tyrosine Phosphorylation-regulated Kinase 1A by Calpain I: A MOLECULAR MECHANISM LINKED TO TAU PATHOLOGY IN ALZHEIMER DISEASE - Jin, Nana (J Biol Chem, 2015)
Hyperphosphorylation and dysregulation of exon 10 splicing of Tau are pivotally involved in pathogenesis of Alzheimer disease (AD) and/or other tauopathies. Alternative splicing of Tau exon 10, which encodes the second microtubule-binding repeat, generates Tau isoforms containing three and four microtubule-binding repeats, termed 3R-Taus and 4R-Taus, respectively. Dual specificity tyrosine-phosphorylation-regulated kinase 1A (Dyrk1A) lies at the Down syndrome critical region of chromosome 21. Overexpression of this kinase may contribute to the early Tau pathology in Down syndrome via phosphorylation of Tau and dysregulation of Tau exon 10. Here, we report that Dyrk1A was truncated at the C terminus and was associated with overactivation of calpain I in AD brain. Calpain I proteolyzed Dyrk1A in vitro first at the C terminus and further at the N terminus and enhanced its kinase activity toward Tau via increased V(max) but not K(m). C-terminal truncation of Dyrk1A resulted in stronger activity than its full-length protein in promotion of exon 10 exclusion and phosphorylation of Tau. Dyrk1A was truncated in kainic acid-induced excitotoxic mouse brains and coincided with an increase in 3R-Tau expression and phosphorylation of Tau via calpain activation. Moreover, truncation of Dyrk1A was correlated with an increase in the ratio of 3R-Tau/4R-Tau and Tau hyperphosphorylation in AD brain. Collectively, these findings suggest that truncation/activation of Dyrk1A by Ca(2+)/calpain I might contribute to Tau pathology via promotion of exon 10 exclusion and hyperphosphorylation of Tau in AD brain.